Air and Vacuum Annealing Effect on the Highly Conducting and Transparent Properties of the Undoped Zinc Oxide Thin Films Prepared by DC Magnetron Sputtering - Radjehi, Lamia; Aissani, Linda; Djelloul, Abdelkader; Saoudi, Abdenour; Lamri, Salim; Nomenyo, Komla; Lerondel, Gilles; Sanchette, Frédéric (Metallurgical and Materials Engineering, 2023)
In this study, we aim to investigate the effect of zinc interstitials (Zni) and oxygen vacancies (VO) on the ZnO electrical conductivity. ZnO films were synthesized via DC magnetron sputtering process using pure Zn target in gases mixture of Ar/O2 = 80/17.5 (sccm). In order to improve the optical and electrical prosperities, the obtained films were subjected to air and vacuum annealing treatment. Several techniques such as field emission scanning electron microscopy (FESEM), Grazing Incidence X-ray Diffraction (GIXRD), Raman spectroscopy, photoluminescence spectroscopy (PL) and UV-visible were used to study the influence of heat treatment on structural and physical properties of ZnO films. Electrical conductivity of ZnO thin films was determined by measuring the sheet resistance and thickness of the films. XRD results confirm the synthesis of annealed ZnO films of the hexagonal structure with a preferential orientation along the (002) plane. The average crystallite size is altered between 22.6 to 28.4 nm dependent on the plan orientation of the ZnO film. Morphology and crystallinity of the ZnO structure could efficiently control the transmittance, electrical resistivity and optical band gap. As deposited ZnO film showed a lower electrical resistivity of 2.72×10-3 Ωcm due to the Zn-rich conditions. Under vacuum annealing, a combination of low resistivity (1.17×10-2 Ωcm) and better optical transmittance (87 %) are obtained. ZnO films developed in this study with high transmittance and low resistivity and good electro-optical quality supports their use in transparent and conductive electrode applications. The plan presentation was visualized using Vesta, with the lattice parameter set as follows: a = b = 3.249 Å; c = 5.207 Å; α = β = 90°; γ = 120°. Based on the construction and optimization of primitive cells, the supercells were constructed and then optimized. Finally, (002) and (103) planes were cut and the planar supercell structure was constructed. In order to make a plane representation for the solid bulk with 10 Å of thickness.